Carry on editing. Issue 1 (22nd June 2018) - Greenfield, Andy
Abstract: Introduction or background: Genome editing facilitates alterations to DNA, large or subtle, in a precise fashion. In its most popular form it uses the programmable endonuclease system, CRISPR/Cas9. Edits can be made to any genome, including the human genome. This raises the possibility of genome editing in human embryos in both a research and reproductive context. Sources of data: All reports of genome editing in human embryos are included here, along with key papers examining the science and ethics of human genome editing. Areas of agreement: As a basic research tool, genome editing promises to accelerate our understanding of genome biology. It also shows great promise as a means of combatting disease through so-called somatic genome editing. Areas of controversy: Genome editing could be used to prevent human disease transmission in a reproductive context. Such germ line interventions are opposed by some, for a number of reasons. Some of these reasons are discussed and a comparison is made with preimplantation genetic diagnosis (PGD). Growing points: It is important that scientists, clinicians, bioethicists and other stakeholders engage widely with all those with an interest in genome editing. Areas timely for developing research: In addition to offering new insights into human biology, basic (fundamental) research will deliver expertise allowing ever more precise and controllable genome editing methodologies and allied technologies. A range of clear and accessible ethical frameworks must be developed and scrutinized as part of a wider societal debate about possible applications of genome editing. In the UK, human reproductive genome editing can only take place if a change to primary legislation occurs. Inclusive discussions and assessments, involving difficult scientific and ethical concepts, must form part of any democratic decision.